2016
DOI: 10.1179/1743284715y.0000000061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retained austenite on wear resistance of nanostructured dual phase steels

Abstract: Nanostructured super bainitic and quenching–partitioning (Q&P) martensitic steels with a significant amount of retained austenite obtained by low temperature bainitic transformation and Q&P respectively were studied to explore the effect of retained austenite on stirring wear resistance. The results suggest that the Q&P martensitic steel significantly enhanced the hardness of the worn surface (from 674 to 762 HV1) and increased the thickness of the deformed layer (∼3.3 μm), compared to the nanostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…The bainite and retained austenite were further refined. As part of the friction energy was absorbed for the transformation of retained austenite and refinement of the microstructure, less energy was available for nucleation and propagation of subsurface cracks [ 39 ]. The wear process had no significant effect on the microstructure of the substrate, which indicated that both hardness and microstructure contribute to improving the tribological properties of the laser forming repaired samples.…”
Section: Resultsmentioning
confidence: 99%
“…The bainite and retained austenite were further refined. As part of the friction energy was absorbed for the transformation of retained austenite and refinement of the microstructure, less energy was available for nucleation and propagation of subsurface cracks [ 39 ]. The wear process had no significant effect on the microstructure of the substrate, which indicated that both hardness and microstructure contribute to improving the tribological properties of the laser forming repaired samples.…”
Section: Resultsmentioning
confidence: 99%
“…Optimisation of production process for nanostructured bainitic steel products for various applications -including armour components, especially in the scope of chemical composition and final heat treatment parameters, is still the subject of research in many scientific centres (e.g. [1][2][3][4][5][6][7]). Understanding the material properties determined in static and dynamic laboratory tests that determine resistance to high-energy impact (e.g.…”
Section: Przedmiotem Artykułu Jest Ustalanie Korelacji Pomiędzy Właścmentioning
confidence: 99%
“…Without regard to the welding limit, continuously cooled carbide-free bainitic steel is a kind of potential candidate for railway applications owing to its higher fracture toughness and fatigue resistance [ 2 , 3 , 4 ]. In addition, it has been reported that the thickness of bainitic lath can achieve to the nanometer level by the isothermal heat treatment [ 4 , 5 , 6 ]. These bainitic steels perform better mechanical properties than continuous cooling bainitic steels.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [ 30 ] considered that bainitic steels had excellent properties by blunting the crack tip on account of the presence of RA. While, some researchers believed that the wear resistance of bainitic steels was determined by the content of RA [ 5 , 30 ], other studies suggested that the stability of RA indeed played a significant role on promoting the damage resistance [ 2 ] and wear resistance [ 6 , 27 , 28 ] due to the TRIP effect. However, it is still elusive how the contact stress and slip ratio affect the transformation of RA in the bainitic steels.…”
Section: Introductionmentioning
confidence: 99%